CRYPTOART: innovation and boldness in the digital art business - Silva, Diogo de Jesus da; Pinto, Giuliano Scombatti (Revista Interface Tecnológica, 2021)
Cryptoart has stood out this year due to the security and growth opportunity it promises, in addition, large companies and artists entered the business as a result of the pandemic. Despite their advantageous promises, the transactions consume a large amount of electricity, which causes greater release of carbon dioxide into the environment. The purpose of this research is to present its concept, discuss transaction costs and discover the technology behind this growing digital art market, as well as the different possibilities that platforms have to work with it. In order to achieve that, websites, articles and books that address blockchain, NFTs and their impacts were used. From there, the future of digital collectibles is discussed, showing the growth of their popularity and the migration of one of the main cryptoarts transaction platforms, in order to reduce their energy consumption. In the end, it is concluded that this business has great potential and in order to achieve greater success, changes will be needed to attract more users.
Keywords: cryptoart; NFT; blockchain; consensus protocols